Hydrogen-powered vessels in green maritime decarbonization: policy drivers, technological frontiers and challenges - Zhibing Zhou; Jin Tao (Frontiers in Marine Science)
The global shipping industry is transitioning toward decarbonization, with hydrogen-powered vessels emerging as a key solution to meet international emission reduction targets, particularly the IMO’s goal of reducing emissions by 50% by 2050. As a zero-emission fuel, hydrogen aligns with international regulations such as the IMO’s greenhouse gas reduction strategy, the MARPOL Convention, and regional policies like the EU’s Emissions Trading System. Despite regulatory support and advancements in hydrogen fuel cell technology, challenges remain in hydrogen storage, fuel cell integration, and operational safety. Currently, high-pressure gaseous hydrogen storage is the most viable option, but its spatial and safety limitations must be addressed. Alternative storage methods, including cryogenic liquid hydrogen, organic liquid hydrogen carriers, and metal hydride storage, hold potential for application but still face technical and integration barriers. Overcoming these challenges requires continued innovation in vessel design, fuel cell technology, and storage systems, supported by comprehensive safety standards and regulations. The successful commercialization of hydrogen-powered vessels will be instrumental in decarbonizing global shipping and achieving climate goals.